The Role of Human Resource Management in Implementing the Merdeka Curriculum: A Deep Learning Approach in Elementary Education at Polewali Mandar - Mesrawati Rifai; Rivai Makduani; Verawaty Verawaty; Abdul Wahab; Andi Makkulawu Panyiwi Kessi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study examines how human resource management (HRM) practices enable the successful implementation of Indonesia’s Merdeka Curriculum to support deep learning in elementary schools. Using a qualitative multiple-case study design, data were collected from four elementary schools in Palu City, Indonesia. The data sources included interviews with school leaders and teachers, classroom observations, and relevant district-level policy documents. Data were analyzed through thematic analysis to identify patterns in HRM practices related to curriculum implementation. The findings reveal four interdependent themes: strategic HRM alignment, professional development transformation, leadership and school culture, and systemic support and constraints. These themes form an integrated HRM–Deep Learning Synergy model, illustrating a continuous relationship in which supportive policy environments sustain teacher recruitment, capacity building, and collaborative leadership. The study also finds that weaknesses in one component—such as limited professional development or rigid administrative structures—can disrupt the overall cycle and reduce curriculum effectiveness. This research contributes to the literature on educational leadership, HRM, and deep learning by offering practical implications for policymakers and school leaders seeking to transform schools into learning organizations that foster higher-order thinking and meaningful learning.